2022
DOI: 10.1007/s12200-022-00021-8
|View full text |Cite
|
Sign up to set email alerts
|

Improved transient electroluminescence technique based on time-correlated single-photon counting technology to evaluate organic mobility

Abstract: The transient electroluminescence (EL) technique is widely used to evaluate the carrier mobility in the field of organic light emitting diodes. The traditional analog detection strategy using oscilloscopes is generally limited since the background noise causes an underestimation of the mobility value. In this paper, we utilize time-correlated single-photon counting (TCSPC) to probe the transient EL for mobility calculation. The measurements on tris(8-hydroxyquinoline) aluminum (Alq3) show that the electron mob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 31 publications
(31 reference statements)
0
3
0
Order By: Relevance
“…Therefore, the EUE of NMZ-based derivatives might be ascribed to the synergistic interaction from luminescent singlet excitons (LSE) and converted excitons via hRISC and TTA processes. Taking the performance of the 2NpNMZ-based non-doped device as an example, its EUE was 51%, and the delay fluorescence (DF) component in radiative transition was estimated as 9% via a TrEL decay response experiment, 35 as shown in Fig. 5A, which should all originate from the TTA process.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the EUE of NMZ-based derivatives might be ascribed to the synergistic interaction from luminescent singlet excitons (LSE) and converted excitons via hRISC and TTA processes. Taking the performance of the 2NpNMZ-based non-doped device as an example, its EUE was 51%, and the delay fluorescence (DF) component in radiative transition was estimated as 9% via a TrEL decay response experiment, 35 as shown in Fig. 5A, which should all originate from the TTA process.…”
Section: Resultsmentioning
confidence: 99%
“…34 The performance of the non-doped device showed a similar trend with higher EQE (4.19%) employing 2NpNMZ as emitting layers to that in 2AnNMZ (1.83%). Furthermore, combined with their transient EL decay spectra, 35 it showed that the hot-exciton process of these two devices was dominant, indicating a larger Δ E T2T1 could effectively suppress the internal conversion channel of the formed T 2 excitons (T 2 → T 1 ) in the electroluminescent (EL) process. This work confirmed that the “plug-in” effect provided a reference value in setting high-lying triplet energy levels, which might be suitable for the design of other new “hot-exciton” building blocks or emitters.…”
Section: Introductionmentioning
confidence: 97%
“…The transient EL signals were recorded by FLS980 (Edinburgh Instruments) MCS model. [ 25 ] The current density data were recorded by Keysight DSOS104A Digital Storage Oscilloscope.…”
Section: Methodsmentioning
confidence: 99%